2021
DOI: 10.1002/ange.202107657
|View full text |Cite
|
Sign up to set email alerts
|

An Atomic Insight into the Chemical Origin and Variation of the Dielectric Constant in Liquid Electrolytes

Abstract: The dielectric constant is ac rucial physicochemical property of liquids in tuning solute-solvent interactions and solvation microstructures.Herein the dielectric constant variation of liquid electrolytes regarding to temperatures and electrolyte compositions is probed by molecular dynamics simulations.Dielectric constants of solvents reduce as temperatures increase due to accelerated mobility of molecules.F or solvent mixtures with different mixing ratios,t heir dielectric constants either followalinear super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…The dielectric permittivity of the EC solvent is described using the so-sphere model, 34 and varies smoothly from 1.0 near the electrode to that of the bulk solvent which is set to 90.7 as per the experimental value at 298.15 K. 35 For an even closer approximation of the environment in Li-ion batteries, one can consider using the dielectric constant of a mixture of solvents. 36 The so-sphere radius for the transition of the dielectric permittivity is calibrated from the reduction potential of standard reference electrodes (cf. Tables 2 and 3 of ref.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The dielectric permittivity of the EC solvent is described using the so-sphere model, 34 and varies smoothly from 1.0 near the electrode to that of the bulk solvent which is set to 90.7 as per the experimental value at 298.15 K. 35 For an even closer approximation of the environment in Li-ion batteries, one can consider using the dielectric constant of a mixture of solvents. 36 The so-sphere radius for the transition of the dielectric permittivity is calibrated from the reduction potential of standard reference electrodes (cf. Tables 2 and 3 of ref.…”
Section: Computational Detailsmentioning
confidence: 99%
“…56 Yao et al developed an artificial neural network model to predict the dielectric constant of complex electrolytes and revealed that the dielectric constant exhibits a volcano trend with increasing Li-salt contents. 104 On the other hand, periodic DFT methods have great advantages in calculating electrochemical properties dominated by intrinsic material characteristics. However, these methods are too expensive to pay off mesoscopic/macroscopic structural calculations.…”
Section: Prediction Of Electrochemical Propertiesmentioning
confidence: 99%
“…For example, Zhang et al performed unsupervised ML training of mXRD by using the anionic sublattice of Li‐containing compounds as a characteristic input, identifying 16 potential SSEs with ionic conductivity exceeding 10 −4 S cm −1 at room temperature from nearly 3000 compounds 56 . Yao et al developed an artificial neural network model to predict the dielectric constant of complex electrolytes and revealed that the dielectric constant exhibits a volcano trend with increasing Li‐salt contents 104 . On the other hand, periodic DFT methods have great advantages in calculating electrochemical properties dominated by intrinsic material characteristics.…”
Section: Cycling Stabilitymentioning
confidence: 99%
“…[60][61][62][63][64][65][66] Beyond conventional experiments, theoretical simulations have been spread to chemistry, materials science, and energy fields. [67][68][69][70][71][72][73][74][75] Especially, density functional theoretical (DFT) calculations have been widely applied in Li-S batteries, such as probing the adsorption of polysulfides on host materials. 76,77 Additionally, the lithium-ion diffusion barrier and Li 2 S decomposition barrier have been proposed to assess the polysulfides diffusivity and the delithiation kinetics on host materials, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although great progress has been achieved in Li–S batteries during past years, a deep insight into the working mechanism and rational design strategies of sulfur hosts is very lacking 60–66 . Beyond conventional experiments, theoretical simulations have been spread to chemistry, materials science, and energy fields 67–75 . Especially, density functional theoretical (DFT) calculations have been widely applied in Li–S batteries, such as probing the adsorption of polysulfides on host materials 76,77 .…”
Section: Introductionmentioning
confidence: 99%